The difference in signs of temporomandibular joint disorders between Airforce Pilot Corps, Paskhas Corps, and Supporting Corps in Indonesian Airforce - Basaria Manurung; Endang Sjamsudin; Indra Hadikrishna (Journal of Dentomaxillofacial Science, 2021)
Objective: This study aims to analyze the difference in signs of TMJ disorders in Indonesian Air Force soldiers. Material and Methods: This was a cross sectional study. The research subjects were 39 Indonesian Air Force soldiers who were underwent periodic health check up at Lakespra Dr. Saryanto Jakarta who had met the inclusion and exclusion criteria.. The data obtained were tested with one way Anova, Kruskal Wallis and Mann Whitney test by SPSS. Results: The three groups had signs of TMJ disorders in different proportions. The Paskhas Corps had the highest percentage of abnormalities in the examination of muscle palpation, TMJ palpation, and TMJ auscultation of 23%, 23%, and 53.85%, respectively. Meanwhile, the Airforce Pilot had the most abnormalities in mandibular movement, about 92%. The results of statistical tests showed that there were significant differences in the TMJ auscultation examination in the three groups, but not on other examinations. Conclusion: Exercises and heavy physical loads in the Paskhas Corps can affect the masticatory muscles and cause microtrauma in the TMJ resulting in the occurrence of TMJ symptoms is higher.